Influence of Humic Acid on Water Quality and Growth of Algae in Freshwater Ecosystem - Bakhsh, Hamid Khoda (2001)
One of the approaches to improve aquaculture production is through improvement of fertilization program for phytoplankton production and water quality variables. There are serious problems with the use of raw organic fertilizer in ponds and environment. Oxygen depletion, degradation of water quality, reduced light penetration, and spread of diseases frequently occur after large doses of manure are added to a pond at irregular intervals. This study was conducted to investigate the influence of humic acid (HA) on primary productivity (phytoplankton production) and water quality variables in a freshwater aquatic ecosystem. Two experiments were carried out to evaluate effects of humic acid alone or in combination with inorganic (urea and single super phosphate) or organic fertilizer (cow manure) on the phytoplankton productivity. Prior to the experiments, HA contents of cow manure (CM), chicken manure, compost and tropical peat were estimated to determine the suitable source (quantity) for HA extraction. The results showed that tropical peat contained 46.5% (dry weight basis) HA and 11.6-17.2 folds higher than the other organic fertilizers. Humic acid from the tropical peat was used in the subsequent experiments. An experiment was conducted at the Gharehsoo Station of Fisheries Research Centre of Mazandaran (FRCM) in North of Islamic Republic Iran (July and August 1999) to study the effects of HA and inorganic fertilizer (urea and single super phosphate) on growth of selected freshwater phytoplankton and water quality variables. The experiment was carried out in eighteen 1.5 Liter transparent plastic bottles (control , 25 ppm HA+UP, 50 ppm HA+UP, 100 ppm HA, 100 ppm HA+UP, 150 ppm HA+UP). Three species of green algae (Chlorella vulgaria, Scenedesmus quadricauda, and Oocystis solitaria) and a species of blue-green alga (Oscillatoria agardii) were selected for the study. The results showed that highest population (bloom) was achieved in week 3 by 100 ppm HA. All treatments with a combination of HA and urea-phosphate led to a blue-green algal (Oscillatoria agardii) dominancy with a low phytoplankton bloom and low total nitrogen (TN) and total phosphorus (TP) ratio (0.7-1.03). The green algal dominance was associated with a high TN:TP ratio (16-17) in culture media. pH of HA treatment was within the suitable range (7.84-8.51) for phytoplankton production. Light penetration correlated well with blue-green algal population